Functional Characteristics of Blanched Dried Gonda Vegetables (Sphenoclea zeylanica) Using Freeze Drying - I Wayan Ryantama Swastika Braja; Anak Agung Istri Sri Wiadnyani (SEAS (Sustainable Environment Agricultural Science), 2026)
Gonda vegetable (Sphenoclea zeylanica) is a functional food rich in phenolic compounds, flavonoids, tannin, and vitamin C, which contribute to its antioxidant activity. Fresh gonda has a relatively short shelf life therefore, dried gonda products are developed to improve practicality, extend shelf life, and preserve bioactive components. This study employed a Completely Randomized Design (CRD) with a single treatment factor (pre-treatment) consisting of two levels, namely blanching and unblanching. The drying process was carried out using the freeze-drying method. Each treatment was replicated three times, resulting in a total of 6 experimental units. The data were statistically analyzed using an independent two-sample t-test to determine differences conducted to compare the findings with those of previous studies. The results indicated that the blanching pre-treatment combined with the freeze-drying produced the most favorable functional characteristics of dried gonda. These included a moisture content of 13.64%, yield of 16.11%, rehydration capacity of 116.36%, flavonoid content of 0.066 mg QE/g, tannin content of 0.57 mg TAE/g, vitamin C content of 0.19 mg AAE/g, and antioxidant activity of 66,43%. Color analysis showed L and a* values of 23.65 and -29.21, respectively. Sensory evaluation revealed that the color of dried gonda was rated as bright with a scoring value of 3.00 and was well accepted, with hedonic score of 4.47. The texture received a scoring value of 2.00 (slightly soft) and a hedonic score of 3.00 (neutral), while the overall acceptability reached 3.60 indicating a favorable level of consumer acceptance.